Perlindungan Hukum Terhadap Hak Kebebasan Berpendapat di Ruang Digital: Keseimbangan Antara Hak dan Kewajiban Pengguna Media Sosial - Sitti Fausia (Ridwan Institute, 2026)
The rapid development of social media as a digital space has provided broader opportunities for individuals to express opinions and disseminate information publicly. Freedom of expression in the digital sphere is a right protected by law; however, its exercise must be accompanied by compliance with legal obligations and regulatory limitations. This study aims to analyze the role of law in protecting the right to freedom of expression in digital spaces and in maintaining a balance between the rights and obligations of social media users. This research employs a normative juridical method using statutory and conceptual approaches. Data were collected through library research by examining laws and regulations, legal doctrines, and relevant scholarly literature. The findings indicate that law functions as an instrument of social control that regulates the boundaries of freedom of expression while providing legal certainty for social media users. Nevertheless, challenges remain in the implementation of legal protection, including ambiguity in legal interpretation and the rapid advancement of digital technology that outpaces regulatory development. Therefore, strengthening the role of law through regulatory refinement and proportional law enforcement is essential to ensure an orderly and responsible digital space.